Poster 255: Lateral Extra-Articular Tenodesis Staple Risks Penetration of ACL Reconstruction Tunnel. Issue 7 (30th July 2022) - Anderson, Gregory; Barras, Laurel; Graf, Ryan; Moran, Thomas; Gwathmey, F. Winston; Diduch, David; Miller, Mark; MacLean, Ian
Objectives: The purpose of this study was to identify the risk of ACL femoral tunnel penetration by a small Richards staple used for Lateral Extra-Articular Tenodesis (LET) fixation and to determine whether or not the risk varies between two techniques for ACL femoral tunnel creation. Methods: 20 paired fresh frozen cadaver knees underwent ACL reconstruction with a LET using the modified Lemaire technique (Getgood et al. AJSM, Jan 2020). Left and right knees were randomized to ACL reconstruction with femoral tunnel creation by either the accessory anteromedial portal (AMP) technique or the flexible guide pin and reamer method. The femoral tunnels in the accessory AMP technique arm were created using a 7mm offset guide. Both arms used a 10mm reamer and were reamed to a depth of 25mm. After tunnel creation and prior to passing the ACL graft, the LET was performed. This was completed by harvesting an 8cm long and 10mm wide central portion of the IT band which was left attached to its distal insertion on Gerdy's tubercle. This was routed underneath the LCL and fixed with a small Richards staple on the lateral metaphyseal flare proximal and posterior to the LCL insertion. The staple was angled anteriorly and distally. Fluoroscopy was used to obtain a lateral view of the knee to ensure appropriate position of the staple (Figure 1 ). Finally, tunneloscopy was performed from the anteromedial portal to investigate penetration of the staple into the femoral tunnel (Figure 2 ). A Fisher's exact test was conducted to determine if there was any difference in tunnel penetration between tunnel creation techniques. Results: The staple was noted to penetrate the ACL femoral tunnel in 8/20 (40%) extremities. When stratified by tunnel creation technique, the Richards staple violated 5/10 (50%) of the tunnels made via the accessory AMP technique compared to 3/10 (30%) of those created with a flexible guide pin and reamer (p = 0.65). Conclusions: Staple fixation of a LET carries significant risk of penetrating the ACL tunnel that does not vary by the technique of femoral tunnel creation. This raises concerns over the potential effect of the staple on ACL graft fixation and the ACL graft itself.